Analisis Potensi Kecelakaan Kerja Dengan Metode Hazard Identification And Risk Assessment (HIRA) Pada PT Hilon Sumatera: Analysis of Potential Work Accidents with the Hazard Identification And Risk Assessment (HIRA) Method At PT Hilon Sumatra - Zaharuddin; Hasibuan, Yetti Meuthia; Jaya Gulo, Hendri Putra (INVANTRI (Inovasi Dan Pengelolaan Industri), 2025)
Textile construction methods such as reinforcing floors using fiber reinforced concrete (pillow filling materials), crack panels (cotton blankets), high density covers (mortality materials) and geotextiles have been developed. e PT Hilon Sumatra has not met the safety standards. in the workplace and may be subordinate to them. The purpose of this study is to analyze the risks and causes of occupational accidents. The method used in the study is the HIRA (risk and action) method. The HIRA method is used to identify possible risks and provides an assessment of risks based on the level of risk and severity of the problem. Based on the results of the study it was concluded: The results of the study show that in the final stage there is a very high risk in the tube part of the color up to 14 strengths, at the levels risk in the middle risk (M) of 12% . Risk (H) 44% and high risk (E) 44%. Hazard information includes safety information, K3 promotion, K3 training, emergency models, posters, banners, safety letters and safety signs. Currently, the risk management methods that have been introduced include control, the use of ADP and the use of ergonomic work equipment.